STUDY AND EVALUATION OF THE ECONOMIC FEASIBILITY OF THE PHOTOVOLTAIC SYSTEM FOR SOME AREAS LOCATED ON ONE LATITUDE OF IRAQ - Hussein Ali Mohsen, Musadage I. H. Alhemiari (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This paper presents the application of photoelectric system in provinces of Iraq with the same latitude: Babylon, Karbala, and Kut. The work was simulated using HOMER software to find out the economic feasibility and material costs of the photoelectric system, calculated the total net cost of the system, the total annual cost of the system, the cost of the capital, the capacity to convert power in the transformer, the power generation capacity in the panels, the cost of power, the extent of battery productivity, battery life, the number of batteries, the self-charging of the battery, the extent of the production of the solar panel, the excess electricity, and the lack of capacity for these provinces. The results have been very close for all those provinces